Lithium continuation therapy following ketamine in patients with treatment resistant unipolar depression: a randomized controlled trial - Costi, Sara; Soleimani, Laili; Glasgow, Andrew; Brallier, Jess; Spivack, John; Schwartz, Jaclyn; Levitch, Cara F.; Richards, Samantha; Hoch, Megan; Stade, Elizabeth C.; Welch, Alison; Collins, Katherine A.; et al. (Neuropsychopharmacology (New York, N.Y.), 2019)
The N-methyl-D-aspartate (NMDA) receptor antagonist ketamine is associated with rapid but transient antidepressant effects in patients with treatment resistant unipolar depression (TRD). Based on work suggesting that ketamine and lithium may share overlapping mechanisms of action, we tested lithium compared to placebo as a continuation strategy following ketamine in subjects with TRD. Participants who met all eligibility criteria and showed at least an initial partial response to a single intravenous infusion of ketamine 0.5 mg/kg were randomized under double-blind conditions to lithium or matching placebo before receiving an additional three infusions of ketamine. Subsequent to the ketamine treatments, participants remained on lithium or placebo during a double-blind continuation phase. The primary study outcome was depression severity as measured by the Montgomery-Åsberg Depression Rating Scale compared between the two groups at Study Day 28, which occurred ~2 weeks following the final ketamine of four infusions. Forty-seven participants with TRD were enrolled in the study and underwent an initial ketamine infusion, of whom 34 participants were deemed to have at least a partial antidepressant response and were eligible for randomization. Comparison between treatment with daily oral lithium (n = 18) or matching placebo (n = 16) at the primary outcome showed no difference in depression severity between groups (t = 0.11, p = 0.91, 95% CI [-7.87, 8.76]). There was no difference between lithium and placebo in continuing the acute antidepressant response to ketamine. The identification of a safe and effective strategy for preventing depression relapse following an acute course of ketamine treatment remains an important goal for future studies.